The story of mathematics : from creating the pyramids to exploring infinity - Rooney, Anne, ....- (London : Arcturus, 2014)
Author Anne Rooney weaves together mathematical strands from every age and culture into a fascinating and entertaining narrative, which coincidentally tells the story of how mankind moved on from cave dwelling to the life of today. Great mathematical thinkers covered include Napier, Liu Hui, Aryabhata, Galileo, Newton, Russell, Einstein, Riemann, Euclid, Carl Friedrich Gauss, Charles Babbage, Montmort, Wittgenstein, and many, many more. This book will appeal to a general audience and math enthusiasts as well as to parents who wish to enthuse their children about the subject. It is beautifully illustrated throughout in full color.
Previous edition: 2008.
Includes index.
Keywords: Mathematics -- History; Wiskunde -- Geschiedenis